The Sumerian dam-kàr-e-ne of the Third Ur Dynasty - Forde, Neis Walter
Ph.D.; Advisor: T. B. Jones; University Microfilms Order No. 65-7915. Microfilm $3.00; Xerography $7.60; Dissertation Abstracts 26/9 (Ann Arbor, Mich., March 1966) 5387-5388.